Preferences for Japanese Baby Powdered Milk in Vietnam - Dinh, Linh Dieu; Lee, Brice Tseen Fu (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
In recent years, the Vietnamese market has seen a significant influx of Japanese baby powdered milk. Understanding the position of Japanese baby powdered milk compared to domestic and other imported brands is crucial. This study explores key product attributes perceived by Vietnamese consumers and examines how the Japanese brand origin influences purchase intentions. While consumer behavior studies are common, research focusing on Japanese baby powdered milk in Vietnam is limited. This research reviews past findings and formulates hypotheses on factors leading to the purchase of Japanese powdered milk. Key attributes like brand origin, nutrition labels, safety certificates, and price are analyzed in scenarios reflecting real-life choices by Vietnamese parents. Data from 109 social media responses were analyzed using Choice Experiment and Structural Equation Modeling to reveal relationships between Japanese brand origin and purchase intention. The results show a preference for Japanese powdered milk over domestic and other imported brands, highlighting the critical role of nutrition labels and safety certificates. This study suggests Japanese companies should leverage their brand origin in marketing strategies in Vietnam.